Determination of Physical Chemical Properties and Antioxidant Potential of Bajakah Tampala Herbal Tea (Spatholobus littoralis Hassk) - Lucky Hartanti; Rafdinal Rafdinal; Asri Mulya Ashari; Rita Kurnia Apindiati; Gusti Eva Tavita; Andi Denisa Fadliah Nur; Warsidah Warsidah (STIKes Surya Global Yogyakarta, 2022)
Herbal tea is one of the functional drinks, which is consumed for the purpose of preventing or treating disease. The number of side effects that arise from the consumption of drugs made from synthetic or chemical materials has led to a tendency for people to return to consuming herbal plants as a solution to health problems. The purpose of this study is to make tea from the roots of tampala (Spatholobus littoralis Hassk) and to test the physical and chemical properties, organoleptic examination and determination of antioxidant activity. Testing of physical and chemical properties including water content, ash content and pH of the preparation, organoleptic examination including taste and odor and color of the brewed solution and determination of antioxidant activity was carried out using the DPPH method (2,2-diphenyl-1-picrylhydrazil). The results of the physicochemical test of tampala tea showed that a pH of 6.8, water content of 7.63%, ash content of 7.7%. On organoleptic examination, the tea using the brewed water showed a slightly sour taste, a characteristic wood smell and a brownish yellow color. Based on the physical and chemical character of the tampala herbal tea test results, it meets the requirements of SNI No. 3836 of the 2013 National Standardization Agency, while the antioxidant test results of the tampala herbal tea was obtained an IC50 value (Inhibition Concentration 50) of 89.63 ppm, included in the category of strong antioxidant potential, because it is in the category of strong antioxidant potential. in the range of 50-100 ppm.